Analisis semiotik Charles Sanders Pierce mengenai logo baru Perpustakaan Nasional Republik Indonesia - Rully Khairul Anwar; Irene Alifa Hapsari; Dian Sinaga (Jurnal Kajian Informasi dan Perpustakaan, 2018)
The Logo is an identity of the institution that to represent the history and the culture and as a promotion media to introducing the institution to the public. The Indonesian National Library has made new logo as a representation this library. This study aimed to find out the meaning of the Indonesian National Library the new logo by determining the symbols, meaning of the symbols, and meaning of the construction of the logo of the Indonesian National Library as the identity of the institution that emphasizes public service. This study used Charles Sanders Pierce's semiotic analysis method through the qualitative approach. Data collection techniques used in this study were observation and literature study. The results showed that the logo of the Indonesian National Library comprised symbols which symbolized star’s as natural light and the open books as library wealth. The second this symbols which symbolized the library as a life-long learning; books were the windows of the world, the light in educating the nation, the depth of knowledge, a progressive and advanced institution, an opening of mind and knowledge. Symbols that showed the meaning of the Indonesian National Library identity were graphic elements of books, stars, green, blue, and black colors. Symbols that did not describe a character were the graduations. In conclusion, the meaning of each sign is built into a single meaning that the Indonesian National Library as an institution which always prioritizes public service with graphic elements of open books and the Indonesian National Library new logo.